Effect of the combination of curcuminoid and essential oil on the serum ureum and creatinine level of patientswith osteoarthritis - Kertia, Nyoman; ., Danang (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2011)
The curcuminoid of Curcuma domesticaVal. rhizome and the essential oil of Curcuma xanthorrhizaRoxb. rhizome can be used for rheumatic treatment,but no enough data regarding those side effects. This study aimed to determine the efect of curcuminoid of Curcuma domestica Val. combined with essential oil from Curcuma xanthorriza Roxb. to the serum ureum and creatinine level of patients with osteoarthritis. This treatment was compared tothat of piroxicam. This was a Prospective Randomized Open end Blinded Evaluation (PROBE), involving 38 patients with knee osteoarthritis.The treatment group were given the combination of 15 mg curcuminoid of Curcuma domestica Val. and 100 mg essential oil of Curcuma xanthorrhizatwice daily for two weeks. The control group were given 10 mg piroxicam twice daily for two weeks. In the treatment group the serum ureum level decreased 4.58±6.20% mg, while in the control group the ureum level increased 1.68±8.24% mg. In the treatment group the serum creatinine level decreased 0.12±0.36% mg, while in the control group the creatinine level increased 0.18±0.29% mg. Decreasing of serum ureum level in the treatment group was significantly different compared to increasing of that level in the control group (p<0.01). Decreasing of the creatinine level in the teatment group was significantly different compared to increasing of that level in the control group (p<0.01).Key words: Curcuminoid, Essential Oil, Ureum, Creatinine, Osteoarthritis